Drug-Drug Interactions and Prescription Appropriateness in COVID-19 ICU Patients in a Tertiary Care Hospital - Moza, Shvesh; Mali, Pankaj K.; Pattar, Pratima M.; Panchal, Suraj B.; Chikkannasetty, Somashekara S. (Pharmacology and Clinical Pharmacy Research, 2024)
Severe Coronavirus disease 2019 (COVID-19) management has been challenging due to varying treatment protocol. Additionally, co-morbidities and older age group receiving polypharmacy increases the risk for drug-drug interactions (DDIs). With limited DDI research studies in Indian setup, we aimed to assess the frequency and severity of potential DDIs in COVID-19 ICU patients. This was a retrospective, observational study conducted in a tertiary care hospital, Karnataka, India. Case record of all patients aged ≥18 years with COVID-19 disease admitted to the COVID-19 ICU during March 2021 to July 2021 and treated with two drugs at least were included. A total of one hundred ninety one medical records of COVID-19 patients confirmed by RTPCR were reviewed from medical record department. DDIs were assessed by validated INTERCheck® web system and prescription appropriateness by Beers criteria. Among 191 COVID-19 treated patients, a total of 1049 pDDIs were recorded. Thirty nine percent of the total interactions were classified as potentially severe (class C + class D). Severe pDDIs increased significantly (140 to 274; p < 0.001) during hospitalization. Consistently, a significant increase in drug interactions trend was observed during hospitalization (432 to 617; p < 0.001). Hence, this study concludes that the severe pDDIs increased significantly during hospitalization and consistent increase in overall (Class A, B, C D) drug interactions trend was observed during hospitalization largely because of the drugs managed to treat comorbidities. Therefore, web based system with multidisciplinary team of expertise may be adopted in hospitals for regulating the dosage of interacting drugs and selecting substitute for over all optimizing the therapy.